1990
DOI: 10.1002/srin.199000388
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stress triaxiality upon ductile crack propagation

Abstract: In this report a brief overview on the influence of the specimens’ geometry and, therefore, the stress triaxiality upon the elastic plastic fracture mechanics parameters and the stable crack extension will be given. Corresponding references to detailed publications will be given. First, possible variations of testing specimens’ geometries will be discussed and later the influence of stress state upon the plastic strain in case of failure will be quantitatively analysed for axialsymmetric, circumferrentially no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Notched round bars experience higher triaxiality than un-notched round bars when subjected to tension. The fracture strains of notched specimens are found to be less than those of the un-notched round bars (Hancock and Mackenzie, 1976;Holland et al, 1990). The relationship between the plastic strain at fracture and the hydrostatic pressure is determined from a particular load condition -the generalized tension.…”
Section: Hydrostatic Pressure Sensitivitymentioning
confidence: 98%
“…Notched round bars experience higher triaxiality than un-notched round bars when subjected to tension. The fracture strains of notched specimens are found to be less than those of the un-notched round bars (Hancock and Mackenzie, 1976;Holland et al, 1990). The relationship between the plastic strain at fracture and the hydrostatic pressure is determined from a particular load condition -the generalized tension.…”
Section: Hydrostatic Pressure Sensitivitymentioning
confidence: 98%
“…Many experimental investigations have demonstrated that the fracture strain (see Eq 6) strongly depends on stress triaxiality (Ref [37][38][39][40][41]. Two methodologies are typically used to evaluate the stress triaxiality: the first one is analytical and is based on the Bridgman analysis (Ref 42) and the second is numerical and based on FE simulations.…”
Section: 21mentioning
confidence: 99%
“…It can be observed [25][26][27][28] that the stress triaxiality can provide a simple parameter to identify the type of collapse: stress triaxiality lower than zero (t = 0 corresponds to a pure shear situation) produces a shear-type plastic flow collapse, which can be identified as a special case of fracture process, while positive triaxiality produces a void formation-type fracture process (fracture along a direction normal to the principal stress) [27,28]. Experimental observations [21] have shown that fracture never occurs for t £ -1 3.…”
mentioning
confidence: 93%